2016
DOI: 10.5946/ce.2016.023
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Biliary Metal Stents

Abstract: Many advances have been achieved in biliary stenting over the past 30 years. Endoscopic stent placement has become the primary management therapy to relieve obstruction in patients with benign or malignant biliary tract diseases. Compared with plastic stents, a self-expandable metallic stent (SEMS) has been used for management in patients with malignant strictures because of a larger lumen and longer stent patency. Recently, SEMS has been used for various benign biliary strictures and leaks. In this article, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 75 publications
(95 reference statements)
1
29
0
Order By: Relevance
“…Important causes of distal malignant biliary obstruction include pancreatic cancer, distal cholangiocarcinoma, ampullary cancer, and, less commonly, gallbladder cancer and metastasis [90]. Methods for palliative biliary drainage include surgical drainage, percutaneous transhepatic drainage, and endoscopic transpapillary drainage.…”
Section: Medicalmentioning
confidence: 99%
See 3 more Smart Citations
“…Important causes of distal malignant biliary obstruction include pancreatic cancer, distal cholangiocarcinoma, ampullary cancer, and, less commonly, gallbladder cancer and metastasis [90]. Methods for palliative biliary drainage include surgical drainage, percutaneous transhepatic drainage, and endoscopic transpapillary drainage.…”
Section: Medicalmentioning
confidence: 99%
“…They have little risk of migration and have reported successful deployment rates of 85.2% to 100% [89]. However, patency rates beyond 3 months are poor, requiring maintenance exchanges to ensure continued adequate ductal drainage [89,90]. The use of plastic stents may be preferable in cases of obstructive lesions that may respond to chemotherapy or radiotherapy (eg, lymphoma) or in patients whose histological diagnosis has yet to be made.…”
Section: Medicalmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with a life expectancy of more than 4 months, SEMS are superior to plastic stents [13]. Two recent SRMAs comparing SEMS and plastic stents (11 retrospective and prospective studies, n = 947 and 20 RCTs, n = 1713, respectively) found SEMS to be associated with longer stent patency, lower re-intervention rates and lower rates of cholangitis [14,15].…”
Section: Endoscopic Therapiesmentioning
confidence: 99%